Characterization of four types of MLV-derived porcine reproductive and respiratory syndrome viruses isolated in unvaccinated pigs from 2016 to 2020. (January 2021) - Chen, Nanhua; Li, Xinshuai; Xiao, Yanzhao; Li, Shubin; Zhu, Jianzhong
Abstract: Modified live vaccines (MLVs) have been utilized to combat porcine reproductive and respiratory syndrome (PRRS), which raises a serious concern about the MLV-derived PRRS virus (PRRSV) isolates. During the routine investigation of PRRSV in China, four lung samples collected from unvaccinated diseased pigs from 2016 to 2020 were detected as PRRSV positive. The PRRSVs shared high ORF5 identities to CH-1R, JXA1-R, TJM-F92 and RespPRRS MLV vaccines, respectively. The viruses were isolated in Marc-145 cells and denominated as SD1612-1, JS1703-21, JSTZ1907-714 and JSYC20-05-1. Genome comparison confirmed that these isolates share the highest genomic homologies to CH-1R (97.96%), JXA1-R (99.64%), TJM-F92 (99.00%) and RespPRRS MLV (99.57%) than any other known isolates. Genome-based phylogenetic analysis showed that SD1612-1 and CH-1R, JS1703-21 and JXA1-R, JSTZ1907-714 and TJM-F92, JSYC20-05-1 and RespPRRS MLV were grouped in the same branches. In addition, amino acids unique to corresponding vaccine attenuations were also identified in our isolates. Noticeably, amino-acids potentially associated with the virulence revision from MLV strains to parental virulent viruses were also identified in the MLV-derived isolates. Our results confirm that the four types of MLV-derived isolates are circulating and evolving in Chinese swine herds for years, which highlights the necessity for the fair use of PRRS MLVs. Highlights: Four PRRSV isolates from unvaccinated pigs were identified as MLV-derived viruses. These isolates share the highest genome identity with four commercial vaccines. Genome-based phylogenetic analysis showed that they are grouped in the same branches with MLV strains. Unique amino acids associated with MLV attenuation were identified in our isolates. Unique amino acids potentially associated with virulence reversion were also determined.